Smart Laboratory Using Radio Frequency Identification (RFID) Based on The Internet of Things - Firmansyah M S Nursuwars; Reza Fragaria Audika; Sutisna Sutisna; Imam Taufiqurrahman (Universitas Pendidikan Indonesia, 2022)
In Indonesia, traditional methods are still commonly used for managing laboratories. This has resulted in various issues, such as the loss of keys, and has hindered the efficiency of these laboratories. However, the integration of technology has the potential to improve laboratory management by up to 33%. A modernized laboratory system, known as an